Integrating evidence and causal mapping of factors that influence medication decision-making by pregnant women at risk of hypertensive disorder: protocol for a scoping review - David K Stevenson; Gary L Darmstadt; Yin Jien Lee; Anita Taft (BMJ Open, 2024)
Introduction In 2018, the American College of Obstetricians and Gynecologists recommended low-dose aspirin to prevent the onset of pre-eclampsia among women who were at high risk. Factors influencing women’s acceptance of this recommendation span multiple sectors and levels. Understanding how these factors interact will help stakeholders design effective population-level intervention strategies. Our study aims to identify and map relationships among factors influencing the medication decisions of pregnant women at risk of hypertensive disorders.Methods and analysis Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) guidelines will be followed for this review. A research librarian developed a comprehensive search strategy to retrieve published and unpublished English studies after 1 January 1980, involving factors that influence pregnant women’s uptake and adherence to medication for gestational hypertensive disorders. This literature includes perceptions, patterns, acceptance, refusal, tendencies, probability and service utilisation. We will search PubMed, Embase, Web of Science and CINAHL. Reference lists of the selected papers will be searched manually to identify more relevant studies. A two-stage independent screening, consisting of title and abstract screening, followed by full-text screening, will be conducted by two independent reviewers to identify eligible articles. Extracted data will be recorded in a customised variable extraction form and input into a Microsoft Access database. The PRISMA-ScR will be used to guide the presentation of the results, which will be presented in a table and causal map to demonstrate the relationships between extracted variables and medication uptake and adherence. A conceptual simulation model will be formulated to validate the logic of the relationships between variables and identify knowledge gaps. Lastly, experts and stakeholders will be invited to critique and comment on the results.Ethics and dissemination This study does not require ethical approval. The full review results will be presented at a relevant conference and submitted to a peer-reviewed scientific journal for publication.